Os efeitos do câmbio flutuante sobre a balança comercial no período de 1999 A 2009 - Brito, Emmanuel Nóbrega de (2010)
This work aims at investigating the effects of floating exchange rates on the Brazilian trade balance from 1999 to 2009, a period that began floating exchange rate regime, establishing the macroeconomic determinants that had the greatest impact on business outcomes in the period. Several events that have caused impacts on the Brazilian exchange rate policy will be studied, such as: change of exchange rate regime in 1999 presidential elections in 2002, the financial crisis in the United States in 2008, among others. Finally it will make an analysis of the coefficients of variation in exchange rates, exports and imports. Based on the authors, Pimentel Gomes (2000) and Garcia (1989), you can make a classification on the level of precision of coefficients.